2020
DOI: 10.1186/s12891-020-03434-8
|View full text |Cite
|
Sign up to set email alerts
|

Is retrospective assessment of health-related quality of life valid?

Abstract: Background: Health-related quality of life (HRQoL) is a commonly used health outcome. For many acute conditions (e.g. fractures), retrospective measurement of HRQoL is necessary to establish pre-morbid health status. However, the validity of retrospective measurement of HRQoL following an intervening significant health event has not been established. The aim of this study was to test the validity of retrospective measurement (recall) of HRQoL by using a test-retest design to measure reliability and agreement b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 30 publications
2
35
0
1
Order By: Relevance
“…These studies find no significant differences in retrospectively and prospectively reported EQ. 5D-scores on a population level [ 31 , 32 ]. To prevent potential bias from patients reporting only small changes in the EQ.…”
Section: Discussionmentioning
confidence: 99%
“…These studies find no significant differences in retrospectively and prospectively reported EQ. 5D-scores on a population level [ 31 , 32 ]. To prevent potential bias from patients reporting only small changes in the EQ.…”
Section: Discussionmentioning
confidence: 99%
“…For example, height and weight were assessed by self-report, which is likely less accurate than objective measurement. However, studies show that web responders usually provide accurate information about themselves [ 63 ]. Relatedly, we do not have information about participants’ specific medical diagnoses, and it may be that such information could have provided important insights into the detected variability in SRH.…”
Section: Discussionmentioning
confidence: 99%
“…The limitations of our study include the handling of the EORTC QOL-C30 questionnaire, which is not designed to be used for retrospective surveys. A comparison of a retrospective and prospective application of another quality of life questionnaire yielded a high agreement [ 39 ]. This questionnaire has been used in a setting very comparable to ours [ 40 ].…”
Section: Discussionmentioning
confidence: 99%